1999
DOI: 10.1074/jbc.274.7.4155
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Compound Origin of Replication at theHMR-E Locus in Saccharomyces cerevisiae

Abstract: 194 -199). In contrast, the sequence elements that may comprise origins in multicellular eukaryotes are largely unknown. The yeast HMR-E region is both a chromosomal origin of replication and a silencer that represses transcription of adjacent genes through a position effect. The analysis presented here indicated that HMR-E had a novel DNA structure that was more complex than defined for other yeast origins, and thus revealed that there is variation in the structural complexity of yeast origins. In contrast to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…In fact, it has been reported that, both on plasmids and in the chromosome, ARS elements separated by as much as 6 kb interfere with each other, so that only one of the two ARS elements fires in any replication cycle (8,9,39). The sequences responsible for the activity of the HMRE ARS are less well defined than the others, but Hurst and Rivier (31) reported that three separate fragments, spanning 865 bp, have ARS activity, while Palacios DeBeer and Fox (45) extended this observation by demonstrating chromosomal replication origin activity for three fragments in HMRE.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been reported that, both on plasmids and in the chromosome, ARS elements separated by as much as 6 kb interfere with each other, so that only one of the two ARS elements fires in any replication cycle (8,9,39). The sequences responsible for the activity of the HMRE ARS are less well defined than the others, but Hurst and Rivier (31) reported that three separate fragments, spanning 865 bp, have ARS activity, while Palacios DeBeer and Fox (45) extended this observation by demonstrating chromosomal replication origin activity for three fragments in HMRE.…”
Section: Discussionmentioning
confidence: 99%
“…However, mutation of the ACS abolishes ARS activity only within a minimal 138-bp fragment containing the silencer elements, i.e., the ORC, Rap1p, and Abf1p binding sites (Fig. 5B) (19,28,33). In other words, if natural sequences flanking this 138-bp minimal fragment are present, the ACS Ϫ mutant retains replicator activity both in the plasmid and on the chromosome.…”
Section: Vol 28 2008mentioning
confidence: 99%
“…The HMR-E silencer is depicted by the black box. The gray boxes surrounding the silencer represent regions that contain near matches to the A-element and contribute to ORC binding and origin firing in HMR-E(A-) (18,26). Natural HMR-E consists of binding sites for ORC (B1/A-element [black box]) and Rap1p and Abf1p (white boxes).…”
Section: Resultsmentioning
confidence: 99%
“…The experiments described above using HMR-E(A-) mutant cells indicated that Sir1p-dependent silencing could tolerate enhanced origin firing, or something about ORC that promoted this origin firing, at HMRa. However, since multiple regions within HMRa can bind ORC in vitro (M. A. Palacios DeBeer, unpublished) and function as origins in vivo (18,26), these experiments could not address whether the same ORC molecule that bound Sir1p could also function in enhanced origin firing. To better address this issue, we used an engineered version of the HMR-E silencer named the synthetic silencer (HMR-SS) that contains a single ORC binding site required for both origin firing and silencing at HMRa (23,32) (Fig.…”
Section: Sir1-dependent Silencing Of Hmr-e(a-) [Sir1 (ϩϩϩ)] Did Not Dmentioning
confidence: 95%
See 1 more Smart Citation